Cone beam computed tomography-based monitoring and management of target and organ motion during external beam radiotherapy in cervical cancer. (January 2019) - Jensen, Nina Boje Kibsgaard; Assenholt, Marianne Sanggaard; Fokdal, Lars Ulrik; Vestergaard, Anne; Schouboe, Annette; Kjaersgaard, Eva Bruun; Boejen, Annette; Nyvang, Lars; Lindegaard, Jacob Christian; Tanderup, Kari
Abstract: Background and purpose: Organ motion is a challenge during high-precision external beam radiotherapy in cervical cancer, and improved strategies for treatment adaptation and monitoring of target dose coverage are needed. This study evaluates a cone beam computed tomography (CBCT)-based approach. Materials and methods: In twenty-three patients, individualized internal target volumes (ITVs) were generated from pre-treatment MRI and CT scans with full and empty bladders. The target volumes encompassed high-risk clinical target volume (CTV-T HR) (gross tumor volume + remaining cervix) and low risk (LR) CTV-T (CTV-T HR + uterus + parametriae + upper vagina). Volumetric Modulated Arc Therapy (VMAT) was used to deliver a dose of 45 Gy in 25 fractions. CBCTs were used for setup and for radiation therapists (RTTs) to evaluate the target coverage (inside/outside the planning target volume). CBCTs were reviewed offline. Estimates of the dose delivered with minimum (point) doses across all fractions to CTV-T HR (aim 42.75 Gy) and CTV-T LR (aim 40 Gy) were assessed. In patients with insufficient dose coverage, re-plans were generated based on previous imaging. Results: Median (range) of the ITV-margins (mean of anterior-posterior margins) related to uterus and cervix was 1.2 (0.5–2.2 and 1.0–2.1) cm. RTTs were able to assess the target coverage in 90% of all CBCTs (505/563). With re-planning, one patient had considerable benefit (12.7 Gy increase of minimum dose) to CTV-T LR_vagina, four patients had improved dose to the CTV-T LR_uterus (1.2–1.8 Gy), and 3 patients did not benefit from re-planning. Conclusions: Daily CBCT-based monitoring of target coverage by the RTTs has proven safe with limited workload. It allows for reduction in the treated volumes without compromising the target dose coverage.